Effect of water-based sol gel method on structural, thermal and conductivity properties of LiNO 3 –Al 2 O 3 composite solid electrolytes - Sulaiman, M.; Rahman, A.A.; Mohamed, N.S. (Elsevier, 2017)
Composite solid electrolytes in the system (1−x)LiNO3–xAl2O3, with x = 0.0–0.5 were prepared by sol gel method. No organic solvents but water was used as medium for the sol preparation. The obtained materials were characterized by X-ray diffraction, differential scanning calorimetry, scanning electron microscopy, Fourier transform infrared spectroscopy and impedance spectroscopy. Structural analysis evidenced amorphous phase of LiNO3 in all composite samples. Traces of crystalline LiAl5O8 and LiAlO2 were also present in the composite samples with x = 0.3–0.5, as indicated by the X-ray diffractograms. The thermal analysis showed that the samples were in a stable phase between ∼48 °C – ∼100 °C and ∼120 °C – ∼220 °C. The conductivity values of the composites were in the range of 10−3 S cm−1 at room temperature to 180 °C. Our study demonstrates that water is suitable for the preparation of the composite solid electrolytes.